PENGARUH INOKULASI MIKORIZA VESIKULA ARBUSKULA (MVA) CAMPURAN TERHADAP KEMUNCULAN PENYAKIT LAYU FUSARIUM PADA TANAMAN TOMAT (Solanum lycopersicum) - Uswatun Hasanah; Purnomowati Purnomowati; Uki Dwiputranto (Scripta Biologica, 2017)
Tomato has an important role to fullfil the nutrition of society. The most important problem in the cultivation of tomatoes is fusarium wilt caused by Fusarium oxysporum it will attacking the plants from nursery to adult. One of the alternative control is use the Vesicles Arbuscular Mycorrhizae (VAM). The success of VAM infection in plants is determined by the dose and the inoculation. The aim of this research is to determine the effect of dose and mixture VAM inoculation to against the emergence of fusarium wilt in tomato plants and to determine the dosage mixture VAM inoculation as the most effective way for controlling fusarium wilt in tomato plants. The method of this research used experimental with completely randomized design. The experimental treatment consists of two types of treatment that are combined with used 5 doses of VAM mixture (0 g/plant, 10 g/plant, 12,5 g/plant, 15 g/plant, 17,5 g/plant) and used two ways of inoculation ( inoculation when the seed is planted and inoculation when transplanting the seeds). Each treatment was repeated 3 times and each test are three plants. The parameters was observed the incubation period of the disease and the intensity of fusarium wilt as the main parameter and the measurement of pH, temperature, humidity room, and the degree of infection as supporting parameters. The results of this research showed that the dosage and inoculation of VAM mixture is not able to reduce the emergence of fusarium wilt on tomatoes, but it was able to extend the incubation period of fusarium wilt on tomato plants a dose with 10 g /plant inoculated plants when the seeds are planted and inoculation when transplanting the seeds.